The Effects of Public Infrastructure and Household Characteristics on Inequality and Infant Mortality in Mexico: What Has Changed Between 1990 and 2005? - Richard S. Meindl; Jose Antonio Roldán Amaro; Cynthia Thompson; Tremaine L. Gregory; Marcela Álvarez Izazaga; Gabriel Saucedo Arteaga (Social Medicine Publication Group, 2010)
The reduction of infant mortality (IM) continues to be a primary goal throughout much of the developing world, and a suite of methods have been proposed with which to achieve it. However, most attempts at IM reduction have taken place within the context of an almost bewilderingly complex regimen of simultaneous changes occurring in the physical environment, sociopolitical structure, and health care. Which of these various elements is truly causal in reducing IM and which may be merely a correlated but nonprimary agent? During the past two decades Mexico has constituted an extraordinary field laboratory with which to decipher the roles of these various potential agents of IM reduction. Health resources include community access to proper drainage, safe drinking water, electrical power, as well as a suite of individual, if highly intercorrelated, family and household characteristics. Despite considerable demographic and socioeconomic heterogeneity, dramatic reductions in IM have been achieved, and additional ones are certainly possible. We weigh the factors that have reduced infant mortality in this country. Particular infrastructure improvements in the Pacific South, the Gulf, and the Yucatan peninsula must be continued. This would impact both inequality and, in turn, infant health and survival in this country.